Lysosomal putative RNA transporter SIDT2 mediates direct uptake of RNA by lysosomes. Issue 3 (3rd March 2016) - Aizawa, Shu; Fujiwara, Yuuki; Contu, Viorica Raluca; Hase, Katsunori; Takahashi, Masayuki; Kikuchi, Hisae; Kabuta, Chihana; Wada, Keiji; Kabuta, Tomohiro
ABSTRACT: Lysosomes are thought to be the major intracellular compartment for the degradation of macromolecules. We recently identified a novel type of autophagy, RNautophagy, where RNA is directly taken up by lysosomes in an ATP-dependent manner and degraded. However, the mechanism of RNA translocation across the lysosomal membrane and the physiological role of RNautophagy remain unclear. In the present study, we performed gain- and loss-of-function studies with isolated lysosomes, and found that SIDT2 (SID1 transmembrane family, member 2), an ortholog of the Caenorhabditis elegans putative RNA transporter SID-1 (systemic RNA interference deficient-1), mediates RNA translocation during RNautophagy. We also observed that SIDT2 is a transmembrane protein, which predominantly localizes to lysosomes. Strikingly, knockdown of Sidt 2 inhibited up to ˜50% of total RNA degradation at the cellular level, independently of macroautophagy. Moreover, we showed that this impairment is mainly due to inhibition of lysosomal RNA degradation, strongly suggesting that RNautophagy plays a significant role in constitutive cellular RNA degradation. Our results provide a novel insight into the mechanisms of RNA metabolism, intracellular RNA transport, and atypical types of autophagy.